Autoimmune Psychosis as a Differential Diagnosis of Primary Schizophreniform Psychosis in Children and Adolescents - Briegel, Wolfgang; Wößner, Rupert; Trollmann, Regina (Zeitschrift für Kinder- und Jugendpsychiatrie und Psychotherapie, 2024)
Objective: Autoimmune psychosis (AP), defined as an isolated schizophreniform psychosis with no or only minimal neurological abnormalities stemming from autoantibody-associated cerebral processes, is a very rare and potentially underdiagnosed disorder in children and adolescents. Methods: This article reports the case of a 13-year-old boy who became acutely ill with a psychotic disorder following a respiratory infection. We describe the diagnosis and course of treatment in detail. Results: Following an extensive interdisciplinary workup, a probable glutamic acid decarboxylase (GAD)-associated AP was diagnosed that ultimately remitted completely with treatment. Conclusions: Autoimmune psychoses remain a relatively uncharted territory for the specialty of child and adolescent psychiatry. Good interdisciplinary cooperation is essential for patients with somewhat atypical psychotic symptoms, both in terms of diagnosis and treatment.
CRIS-Team Scopus Importer:2025-02-04